Strategi Pengembangan Profil Pelajar Rahmatan Lil Alamin dalam Implementasi Kurikulum Merdeka di Madrasah Ibtidaiyah - Annisa Nidaur Rohmah (FAKULTAS AGAMA ISLAM UNIVERSITAS BILLFATH, 2024)
The purpose of this research is to find out 1) the urgency of Rahmatan Lil Alamin Student Profile, 2) Rahmatan Lil Alamin Student Profile Development Strategy, 3) supporting and inhibiting factors in the Implementation of Rahmatan Lil Alamin Student Profile Development Strategy and find out what the solution is in Madrasah Ibtidaiyah. This research is field research, the approach used is a qualitative approach with descriptive methods. The subjects of this research were the head, Deputy Head of Curriculum and teachers of Madrasah Ibtidaiyah, while the objects of this research were 14 Madrasah Ibtidaiyah. Data collection techniques using interviews, observation and documentation. The data analysis technique applies four steps, namely Data Collection, Data Condensation, Data Presentation, Data Verification/Conclusion. The results of this research show that 1) The urgency or importance of the Rahmatan Lil Alamin Student Profile at Madrasah Ibtidaiyah, namely to produce students who are faithful, devout, have noble character, and have a global outlook, as well as a moderate attitude in religion, 2) Development Strategy namely through Intracurricular, Co-curricular and Extracurricular, 3) Supporting Factors in Implementation are high commitment from the Madrasa head and teachers, Religious Culture, Human Resources, Infrastructure, use of information technology and parental support. The inhibiting factor is a lack of administrative control in program preparation, funding and student interactions at home. Solutions for solving these inhibiting factors from an administrative perspective include attending IKM workshops, KKG, studying at other Madrasahs, learning from information technology, collaboration between teachers and consultation with Madrasah supervisors, while the inhibiting factors in terms of funding and student interactions at home have found solutions. by communicating and collaborating with student parents in community forums.